search points attachment profile arrow left arrow right star heart verified symbols equation arrow-down question mark check menu accountancyadministrationagriculturalalgebraallarabicartart_musicbelarusbelarus_altbiologybusinesscatalachemistrychineseeconomicsegzamenglishentrepreneurshipenvironmentethicseuskarafirst_aidfrenchgalegogeographygeologygeometrygermangrammarhealthhistoryindia_langindonesian_langinformaticsitalianjapanesekazachkazach_altkoreanlanguagelatinlawlife_scienceliteraturelogicmathematicsmusicnigerian_langother_languagesotherspedagogicsphilosophyphysical_educationphysicspoliticspsychologyreligionrpa_langrussianrussian_altsciencesecurityskillssocial_sciencesociologyspanishstatisticstechnologytourismtrafficukrainianukrainian_altukrainian_literaturewos_civilisation accountancyadministrationagriculturalalgebraall_1arabicartart_music_2belarusbelarus_altbiologybusiness_2catalachemistry_1chineseeconomicsexam_3englishentrepreneurshipenvironment_2ethicseuskarasecurity_1frenchgalegogeography_4geology_4geometrygermangrammarhealthhistoryindia-langindonesian-langinformaticsitalianjapanesekazachAsset 230koreanlanguagelatinlawlife-scienceliteraturelogic_2mathematicsmusicnigerian-langotherlanguagesother_1pedagogicsphilosophyphysical_educationphysicspoliticspsychologyreligion_1rpa-langrussianrussian_altsciencesecurity_3_mskills_1allsocial_science_5_msociologyspanishstatisticstechnologytourismtrafficukrainianukrainian_altukrainian_literaturewos_civilisation

Ответ

Проверено экспертом

Ответ дан
Universalka

1)frac{-3+sqrt{21} }{6}+frac{-3-sqrt{21} }{6}=frac{-3+sqrt{21}-3-sqrt{21}}{6}=frac{-6}{6}=-1\\-frac{b}{a}=-1\\a=b\\2)frac{-3+sqrt{21} }{6} *frac{-3-sqrt{21} }{6} =frac{(-3+sqrt{21})(-3-sqrt{21})}{6*6}=frac{(-3)^{2}-(sqrt{21})^{2}}{36}=frac{9-21}{36}=-frac{12}{36}=-frac{1}{3}\\frac{c}{a}=-frac{1}{3}\\c=-1\\a=b=3

Ответы и объяснения

Не тот ответ, который тебе нужен?


По всем вопросам пишите на - vashurokk@rambler.ru